A cross-sectional study on stress and burnout among professionals belonging to information technology sector working from home in Tamilnadu, India - R., Abinesh; J., Barathalakshmi; K., Ganesh Kumar; R., Venkat; E., Aarthy; N., Mithun Kumar; R., Buvaneshwari (International Journal Of Community Medicine And Public Health, 2025)
Background: The post-COVID pandemic situation has brought drastic changes in workplace environments around the world with many organizations shifting to work from home (WFH) models. Methods: An online survey was conducted with an invitation to professionals working from home to participate in the study. The questionnaire contained statements regarding their level of comfort in working from home and the statements from the Depression, Anxiety and Stress Scale (DASS-21) and the acceptance and action questionnaire (AAQ-II). A total of 150 responses were statistically analysed. Results: 60.66% of the participants were experiencing various levels of stress, with 8.6% having severe levels of stress; while 60.66% had some level of anxiety, 4% of the participants had severe levels of anxiety. 32% of the respondents had some level of depression while 1.33% had levels indicative of severe depression. Only 40.66% of the respondents reported being comfortable working from home and 46% of the people reported they could not work without disturbances at home. The nature of job, age, gender and parental status all influenced the levels of stress, anxiety and depression in those who worked from home. Conclusions: People who are working from home are stressed, anxious and have various levels of depression as clearly evidenced in this study.